2017
DOI: 10.1080/15459624.2017.1296234
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of patron sound level exposure in loud restaurants, bars, and clubs in New York city

Abstract: Visiting restaurants, bars, clubs, and lounges is a regular part of urban cultural life for residents and tourists alike; however, anecdotal reports and diner surveys suggest that sound levels are excessive and diners dislike them. High sound levels in these venues can contribute to both patron and employee overexposure, and young people may be particularly at risk. To supplement the paucity of literature and data on noise in urban venues, patron noise exposure was measured inside a sample of loud New York Cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…The authors found that the mean LAeq across 59 venues was 92 dB, with a range of 77 dB-107 dB (Spira-Cohen et al, 2017). The peak sound pressure level was recorded to be 114 dB (Spira-Cohen et al, 2017). The LAeq in restaurants, bars, and clubs appears to be, on average, higher than the values obtained from the current study.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The authors found that the mean LAeq across 59 venues was 92 dB, with a range of 77 dB-107 dB (Spira-Cohen et al, 2017). The peak sound pressure level was recorded to be 114 dB (Spira-Cohen et al, 2017). The LAeq in restaurants, bars, and clubs appears to be, on average, higher than the values obtained from the current study.…”
Section: Discussioncontrasting
confidence: 70%
“…Another study indicated children may be at a greater risk of NIHL (Berglund et al, Another study examined noise in busy restaurants, clubs, and bars in New York City. The authors found that the mean LAeq across 59 venues was 92 dB, with a range of 77 dB-107 dB (Spira-Cohen et al, 2017). The peak sound pressure level was recorded to be 114 dB (Spira-Cohen et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Noticeably, Zemke et al (2011) highlight noise as one of the social sustainability challenges prevailed within the commercial foodservice sector. Further research conducted in the USA (Green and Anthony, 2015;Rusnock and Bush, 2012;Scott, 2018;Spira-Cohen et al, 2017) confirms this by showcasing how inadequate management of noise can lead to community and guest dissatisfaction, thus endangering the well-being of these important foodservice stakeholders.…”
Section: Local Food Usementioning
confidence: 97%
“…Specifically, excessive noise levels are evidenced in the findings that, apart from only quarter of commercial foodservice outlets with proper noise level (Rusnock and Bush, 2012), most foodservice businesses exceeded the maximum (85 dBA) recommended noise dose (Spira-Cohen et al, 2017). Such excessive levels not only interrupt guest conversation, disturb the residents' sleep (Sari et al, 2014), but also expose employees to a health risk of hearing loss (Green and Anthony, 2015;Rusnock and Bush, 2012).…”
Section: Local Food Usementioning
confidence: 99%